Anion interaction with ferrocene-functionalised cyclic and open-chain polyaza and aza-oxa cycloalkanes - Beer, P; Cadman, J; Lloris, J; Martinez-Manez, R; Soto, J; Pardo, T; Marcos, MD (2000)
A family of ferrocene-functionalised receptors of different topologies have been used as receptors for anions. The compounds have been designed to contain both amine nitrogen and ether oxygen atoms and comprises from monoaza to pentaaza derivatives both open-chain (L1, L2, L3) or cyclic (L4, L5) and having from one to five ferrocenyl groups. Solution studies directed to determine the protonation constants of L1, L2 and L3 have been carried out in water (0.1 mol dm3 KNO3, 25 °C) and those of L4 and L5 in 1,4-dioxane-water (70:30 v/v, 0.1 mol dm -3 KNO 3, 25 °C). The protonation behaviour of the receptors can be explained taking into account electrostatic considerations. Speciation studies in the presence of phosphate have been carried out in water for L', L2 and L3 and in dioxane-water for L4 and L5. Speciation studies have also been performed in the presence of ATP with L1, L2 and L3 in water. Selectivity of a mixture of receptors against a certain anion is discussed in terms of ternary diagrams. The shift of the redox potential of the ferrocenyl groups as a function of the pH has been studied. The difference between the oxidation potentials at basic and acidic pH has been determined experimentally and is compared with that theoretically predicted using an electrostatic model previously reported. The electrochemical shift in the presence of ATP and phosphate has been measured in water for L1, L2 and L3 and in the presence of phosphate and sulfate in 1,4-dioxane-water for L4 and L5 as a function of the pH. The electrochemical response found against those anions is quite poor with maximum cathodic shifts off. 30tO mV. The electrochemical response induced by HSO4 and H2PO4- has also been studied in acetonitrile solutions where a large cathodic shift for H 2PO 4- up to ca. 200 mV was found. © The Royal Society of Chemistry 2000.